Prospective study of loss of health-related quality adjusted life years in children and their families due to uncomplicated and hospitalised varicella. Issue 6 (3rd February 2023) - Rodrigues, Fernanda; Marlow, Robin; Gouveia, Catarina; Correia, Paula; Brett, Ana; Silva, Catarina; Gameiro, Inês; Rua, Inês; Dias, João; Martins, Marta; Diogo, Rui; Lopes, Teresa; et al.
Highlights: First study to quantify QALY loss due to varicella in hospitalised children. First study to describe QALY loss in the carers of children with varicella. High QALY loss in the family units of children admitted to hospital with varicella. Significant impact on HRQoL of varicella infection in family units. Abstract: Introduction and aims: Although usually benign, varicella can lead to serious complications and sometimes long-term sequelae. Vaccines are safe and effective but not yet included in immunisation programmes in many countries. We aimed to quantify the impact on health-related quality of life (HRQoL) in terms of quality-adjusted life years (QALY) in children with varicella and their families, key to assessing cost-utility in countries with low mortality due to this infection. Methods: Children with varicella in the community and admitted to hospitals in Portugal were included over 18 months from January 2019. Children's and carers' HRQoL losses were assessed prospectively using standard multi-attribute utility instruments for measuring HRQoL (EQ-5D and CHU9D), from presentation to recovery, allowing the calculation of QALYs. Results: Among 109 families with children with varicella recruited from attendees at a pediatric emergency service (community arm), the mean HRQoL loss/child was 2.0 days (95 % CI 1.9–2.2, n = 101) (mean 5.4 QALYs/1000 children (95 % CI 5.3–6.1) and 1.3 days/primary carer (95 % CI 1.2–1.6, n = 103) (mean 3.6 QALYs /1000 carers (95 % CI 3.4–4.4). Among 114 families with children admitted to hospital because of severe varicella or a complication (hospital arm), the mean HRQoL loss/child was 9.8 days (95 % CI 9.4–10.6, n = 114) (mean 26.8 QALYs /1000 children (95 % CI 25.8–29.0) and 8.5 days/primary carer (95 % CI 7.4–9.6, n = 114) (mean 23.4 QALYs/1000 carers (95 % CI 20.3–26.2). Mean QALY losses/1000 patients were particularly high for bone and joint infections [67.5 (95 % CI 43.9–97.6)]. Estimates for children's QALYs lost using the CHU9D tool were well correlated with those obtained using EQ-5D, but substantially lower. Conclusions: The impact of varicella on HRQoL is substantial. We report the first measurements of QALYs lost in hospitalised children and in the families of children both in the community and admitted to hospital, providing important information to guide vaccination policy recommendations.